Enhancing learning through real-world application: experiential learning for INFO 4342 Business Continuity and Disaster Recovery - Talib, Shuhaili (Kulliyyah of Information and Communication Technology, IIUM, 2024)
The Business Continuity and Disaster Recovery (BCDR) course is designed to equip students with the knowledge and skills necessary to ensure an organization can maintain operations despite disruptions caused by incidents or disasters. This course covers strategies and practices that organizations can adopt to prepare before, respond during, and recover after such events. Throughout the course, students will engage in assignments and projects focused on key areas such as risk assessment and business impact analysis (BIA). By the end of the semester, students are expected to apply the theoretical concepts learned to develop a comprehensive BCDR plan for an organization, demonstrating their ability to safeguard business operations in the face of potential threats. Experiential learning is one of the teaching methods applied in this course, allowing students to engage directly with real-world scenarios and learn through hands-on activities. This approach immerses students in practical situations, facilitating learning by doing. In terms of learning styles, this method aligns with kinesthetic learning, which emphasizes active, physical engagement as a key component of the learning process. In this group assignment, students will walk around the KICT building to identify potential risks and capture photographs as evidence. These images will be included in their risk assessment table. Students will identify the sources of risk, assign ratings, and ultimately provide recommendations for improvement to KICT management. This assignment aims to enhance students' critical thinking and their ability to develop practical solutions.